Impact of Drought on the Livelihoods of Farmers in Western Odisha: A Comparison Between Drought and Non-Drought Years - Devi Prasanna Swain; Arunasis Goswami; Bhabesh Chandra Das; Birendra Pratap Singh; Kumar Govil; Suman Sant (Archives of Current Research International, 2024)
The agriculture of our country is increasingly affected due to the irregular climatic variations like drought, flood, etc. which is causing great distress to agriculture farmers financially, socially and emotionally during the period. The present study was undertaken to assess the impact of drought on livelihood of agriculture farmers in drought versus non-drought years in drought prone western Odisha. 194 respondents engaged in agriculture farming as their primary occupation were selected randomly from 3 districts of Western Odisha by stratified random sampling. Ten pertinent questions were selected after due consultation with different stakeholders of the agricultural sector, Govt. officials, University faculties and experts of the field to study the impact of drought. The questions were designed to be answered either in yes or no, which were related to the social, economic, food security and family responsibilities of the agricultural farmer and his family. It was found that the respondents were not able to meet the basic requirements in drought years which could be achieved in non-drought years through agricultural operations. This study also indicated that the basic needs like food, medicine and social needs are severely affected in the drought hit years as compared to the non-drought years. The famers were not even able to purchase medicines in drought hit years. The farmers showed their inability to take care of the basic needs of family during drought. The Government of Odisha may promote secondary sources of livelihood generating options like dairy farming, poultry farming, beekeeping, goat farming, etc., in the drought affected districts of Odisha along with agriculture for meeting basic needs of life during drought period.